The Legal Protection for Third Parties in Confidential Agreements - Alwi Jaya (Leges Privatae, 2025)
This study examines the legal position and protection of third parties affected by confidential agreements under Indonesian contract law. Rooted in the principle of privity of contract, the Indonesian Civil Code recognizes contractual rights and obligations only between the parties directly involved. However, in modern legal and business practices, confidential agreements such as non-disclosure agreements (NDAs), exclusivity contracts, and private arrangements often have unintended consequences for external parties. This normative legal research employs statutory, conceptual, and case approaches to critically analyze the limitations of current regulations and explore comparative models from other jurisdictions, such as the United Kingdom’s Contracts (Rights of Third Parties) Act 1999. The findings reveal a normative gap in Indonesian law that fails to account for the legitimate interests of third parties harmed by undisclosed contractual arrangements. The study recommends the development of a more inclusive legal framework through legislative reform and progressive judicial interpretation, ensuring fairness and legal certainty in contractual relationships involving broader societal impact.